Aspergillus terreus strain improvement for enhanced lovastatin production - Babot, Jaime Daniel (2015)
Cholesterol plays a vital role in body metabolism and membrane transport, and acts as precursor for the synthesis of several key biomolecules. Nevertheless, changes in cholesterol level lead to cardiovascular disorders, like atherosclerosis and hypercholesterolemia, which are currently the main causes of death. This is why controlling cholesterol by inhibition of its biosynthesis is a promising approach. Cholesterol is synthetized from acetyl-CoA through a complex pathway, where the rate-limiting step is the conversion of HMG-CoA to mevalonate, catalyzed by HMG-CoA reductase. This key enzyme is selectively and competitively inhibited by lovastatin, a fungal secondary metabolite used as a hypocholesterolemic which can therefore reduce the risk of cardiovascular diseases. Lovastatin production is normally carried out using selected Aspergillus terreus strains, however industrial process yields may be improved by strain manipulation. Accordingly, the aim of this work was to develop a lovastatin-hyperproducing A. terreus strain. To this end, 107-spores/mL suspensions of lovastatin-producer A. terreus MEC were exposed to UV radiation for different times ranging from 5 to 15 min. Spores were kept in the dark for 30 min, plated onto PDA plates and incubated at 25°C for 48 h. Isolated colonies were transferred to an optimized lovastatin production medium (SQop) containing cheese-whey as substrate and incubated at 25°C for 14 days. Lovastatin was extracted from fungal colonies by using ethyl acetate and converted to its β-hydroxyacid form by alkaline hydrolysis. Organic extracts were preliminary analyzed by TLC, and spot intensities were quantified with ImageJ software. The amount of lovastatin was quantified by RP-HPLC. In a second stage, selected lovastatin hyperproducing mutants were subjected to another mutation cycle and further evaluated. The first obtained 164 putative mutants were comparatively analyzed against the wild-type (WT) A. terreus MEC strain and, according to TLC results, 28 mutants produced 20% or less than it, whilst 20 out of the 164 produced 20% (or higher) more lovastatin than WT. These results, as confronted to the HPLC analyses, confirmed 6 mutant strains with 20%-lower production than WT strain, while only one showed a hyperproducing phenotype. This latter mutant, named C10´-27, produced 168% more (2.35 g/L) lovastatin than WT strain. After a second mutation cycle of A. terreus C10´-27, 157 putative mutants were analyzed. Lovastatin production, as witnessed by RP-HPLC, increased by 20% or higher than the one for C10´-27 for 5 of the obtained mutants. The highest lovastatin titer was achieved by mutant A. terreus S12,5´-9 with a 40% increase over the already improved production of A. terreus C10´-27. These results pave the way to a more efficient lovastatin production by using the selected mutant and may additionally open new perspectives for reducing its production costs.